Keseimbangan Jiwa Raga dalam Pendidikan Islam : Perspektif Al-Ghazali - Faris Sulistiyani; Nasikhin Nasikhin; Nita Yuli Astuti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the importance of balance between body and soul in Islamic education by referring to the thoughts of Imam Al-Ghazali. In Al-Ghazali's view, education is not just a process of transferring knowledge, but a comprehensive effort to form a complete human being through the development of physical, intellectual, and spiritual aspects. The soul is positioned as the main center of personality development, while the body plays a role as a means to support the implementation of spiritual and social tasks. This study uses a qualitative approach with a literature study method to examine in depth the works of Al-Ghazali and other supporting literature. The results of the study show that Al-Ghazali's thoughts on the balance of body and soul are very relevant to be applied in the modern education system, especially in responding to the challenges of dehumanization and value crises. The integration of spiritual and physical dimensions in education can be a solution in forming students who are not only intellectually intelligent, but also emotionally and spiritually mature.